Parasagittal cortical atrophy: a cause of "primary lateral sclerosis" - Helio Lemmi; Richard Daly; Robert Ang (Arquivos de Neuro-Psiquiatria)
A case of severe spastic paraparesis of the lower extremities is presented as an example of the late sequelae of thrombosis of the superior longitudinal sinus. Evidence in support of this presumptive diagnosis is given by analysis of the clinical history and the remarkable pneumoencephalographic findings. This case affords the opportunity to stress the need for caution and restraint in the use of the diagnosis "primary lateral sclerosis".